2018
DOI: 10.1093/inthealth/ihy087
|View full text |Cite
|
Sign up to set email alerts
|

World Pneumonia Day 2011–2016: Twitter contents and retweets

Abstract: Background: Twitter is used for World Pneumonia Day (WPD; November 12) communication. We evaluate if themes of #pneumonia tweets were associated with retweet frequency.Methods: A total of 28 181 original #pneumonia tweets were retrieved (21 November 2016), from which six subcorpora, 1 mo before and 1 mo after WPD 2011-2016, were extracted (n=6721). Underlying topics were identified via latent Dirichlet allocation and were manually coded into themes. The association of themes with retweet count was assessed via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Unfortunately, more than a decade later, pneumonia continues to be a neglected disease, with approximately 800,000 pneumonia deaths in children under 5 years (and 1 million deaths in older people) in 2017 [5]. Several calls to action have been published about pneumonia in the last 10 years to improve the diagnosis, treatment, and prevention of pneumonia worldwide, but there has been limited progress in reducing both pneumonia incidence and mortality [4,6,7,[21][22][23][24][25].…”
Section: The Role Of Social Media As a Platform For Science Communicamentioning
confidence: 99%
“…Unfortunately, more than a decade later, pneumonia continues to be a neglected disease, with approximately 800,000 pneumonia deaths in children under 5 years (and 1 million deaths in older people) in 2017 [5]. Several calls to action have been published about pneumonia in the last 10 years to improve the diagnosis, treatment, and prevention of pneumonia worldwide, but there has been limited progress in reducing both pneumonia incidence and mortality [4,6,7,[21][22][23][24][25].…”
Section: The Role Of Social Media As a Platform For Science Communicamentioning
confidence: 99%
“…14 One particular unsupervised topic modelling method, latent Dirichlet allocation (LDA), 15 has proven particularly popular and successful. LDA has been used for topic mining in studies of health data across an array of data sources, including discussions from condition-specific online support groups [16][17][18][19][20] and more general online discussion platforms, [21][22][23][24][25][26][27][28][29] data about adverse medical events, 30 interview transcripts of patients, 31 32 media articles 33 and survey data. 34 35 Other studies have used LDA to analyse topics in patient-reported concerns as well, in situations where no existing topic information is available.…”
Section: What Does This Paper Add?mentioning
confidence: 99%
“…World Pneumonia Day was first celebrated on 2nd November 2009, to address concerns that childhood pneumonia did not attract levels of support that were commensurate with disease burden, despite causing more deaths than human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), tuberculosis, and malaria combined. Since 2010, World Pneumonia Day has been celebrated every 12th November (3,13,14,17), to raise awareness about the toll of pneumonia on the world's children (26), and to promote interventions to protect against (33), treat, and prevent the disease (21,22), with particular emphasis placed on vaccine development (17,46). World Pneumonia Day 2020 is particularly noteworthy, as this is the first World Pneumonia Day that will be observed during a global pneumonia pandemic.…”
Section: World Pneumonia Daymentioning
confidence: 99%